Kobakan Literasi upaya Membangun Budaya Membaca dalam Meningkatkan Kualitas Kebiasaan Hidup Generasi Alpa Kelurahan Kilasah Kecamatan Kasemen Kota Serang - Ulinnuha, Ulinnuha; Pratama, Rizky Nur; Komariah, Komariah; Rahmi, Lailatur; Linawati, Dwi (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2024)
Life habits determine a person's quality of life. Good habits are proof of the fulfillment of all basic needs such as clothing, food, shelter and education. So bad habits result in poor quality of life. The aim of this community service activity is to improve the living habits of the apla generation in Indonesia, especially in Kilasah Village, Kasemen District, which still has a background in which village children have monotonous habits and tend to be negative through providing literacy training. The method of implementation begins with preparing books, conducting literacy activities, as well as coordinating with the sub-district and Kilasah sub-district community leaders regarding the program, then the implementation is by providing material about literacy culture and reading aloud with the theme of children's character education regarding environmental cleanliness to the next generation of children. forget it, then carry out program evaluation and assistance. This community service has had a significant impact on the target partners, this is proven by the children's enthusiasm for the habit of reading books regularly from the literacy training provided by the team, from the books they read they gain insight, information and positive experiences that will be put into practice in their lives. Thus, they are moved to make changes in character and living habits that are better than before.